Pengaruh Budaya Organisasi dan Motivasi Kerja Terhadap Kinerja Karyawan di Rumah Sakit Dewi Sri Karawang - Ermawati Agustin; Sari Marliani; July Yuliawati (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This research was conducted with the aim of determining the implications between organizational culture and work motivation and employee performance, especially at Dewi Sri Karawang Hospital. This research was conducted using quantitative methods using a sample of 79 respondents. This data was collected through a survey method using a questionnaire to calculate organizational culture, work motivation and its influence on performance. The survey results were analyzed using the multiple linear analysis method where organizational culture (X1) and work motivation (X2) were the independent variables and employee performance (Y) was the dependent variable. The results of research activities explain the good organizational culture variable, with a score of 2,725 and an average of 301, the work motivation variable with a score of 3,172 and an average of 288, and employee performance, with a score of 3,049 and an average of 304. The results of the research show that employee performance at Dewi Sri Karawang Hospital is partially influenced by work motivation, with a significance value of 0.036 <0.05. Organizational culture is also partially influenced, with a significance value of 0.000 <0.05. Furthermore, there is a significant influence between employee performance and organizational culture, with a significance value of 0.000 <0.05.